2012
DOI: 10.1097/mcg.0b013e318247c32f
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Pediatric-onset Inflammatory Bowel Disease

Abstract: Background/Aims There has been no systematic review of natural history studies of pediatric-onset inflammatory bowel disease (IBD). We conducted a systematic review focused on understanding the long-term risks of growth failure, disease reclassification and extension, hospitalizations, cancer and death among patients with childhood IBD. Methods PubMed searches and subsequent data abstraction were performed by 2 independent investigators. Studies published full in english with a 5-year minimum average follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(121 citation statements)
references
References 53 publications
6
109
0
6
Order By: Relevance
“…A significantly higher proportion of patients were diagnosed at a young age in the anti-TNF exposed group. Younger patients with CD often have more aggressive disease that may lead to early surgery and requirement of anti-TNF agents [32][33][34][35] . Despite this, anti-TNF exposed still demonstrated longer median time to surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher proportion of patients were diagnosed at a young age in the anti-TNF exposed group. Younger patients with CD often have more aggressive disease that may lead to early surgery and requirement of anti-TNF agents [32][33][34][35] . Despite this, anti-TNF exposed still demonstrated longer median time to surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Growth retardation occurs in up to 56% of children with CD and up to 10% of children with UC (Abraham et al 2012), and several publications have reported short stature in JIA patients (Simon 2010). The degree of growth impairment is variable and can range from a mild decrease in growth velocity to severe forms of short stature, which can be defined as a body height more than two S.D.…”
Section: Impact Of Inflammation On Bone Growthmentioning
confidence: 99%
“…3,4 There are no data on pediatric health care utilization (HCU) before IBD diagnosis, and limited population-based data on HCU after IBD diagnosis. 5 Exploring the patterns of health care use before chronic disease diagnosis may provide insight into the patterns of diagnostic delay before IBD diagnosis. With increased awareness of IBD and improved access to radiographic and endoscopic diagnostics, it might be expected that time to diagnosis would have been decreasing over recent years.…”
mentioning
confidence: 99%